Developing Visual Novel Game with Speech-Recognition Interactivity to Enhance Students’ Mastery on English Expressions - Elizabeth Anggraeni Amalo; Imam Dui Agusalim; Citra Devi Murdaningtyas (Jurnal Sosial Humaniora, 2017)
The teaching of English-expressions has always been done throughconversation samples in form of written texts, audio recordings, and videos.In the meantime, the development of computer-aided learning technologyhas made autonomous language learning possible. Game, as one ofcomputer-aided learning technology products, can serve as a medium toprovide educational contents like that of language teaching and learning.Visual Novel is considered as a conversational game that is suitable to becombined with English-expressions material. Unlike the other click-basedinteraction Visual Novel Games, the visual novel game in this researchimplements speech recognition as the interaction trigger. Hence, this paperaims at elaborating how visual novel games are utilized to deliver Englishexpressions with speech recognition command for the interaction. Thisresearch used Research and Development (R&D) method withExperimental design through control and experimental groups to measureits effectiveness in enhancing students’ English-expressions mastery.ANOVA was utilized to prove the significant differences between the controland experimental groups. It is expected that the result of this developmentand experiment can devote benefits to the English teaching and learning,especially on English-expressions.